2021
DOI: 10.1080/21655979.2021.1973781
|View full text |Cite
|
Sign up to set email alerts
|

Lumican silencing alleviates tumor necrosis factor-α-induced nucleus pulposus cell inflammation and senescence by inhibiting apoptosis signal regulating kinase 1/p38 signaling pathway via inactivating Fas ligand expression

Abstract: silencing alleviates tumor necrosis factor-α-induced nucleus pulposus cell inflammation and senescence by inhibiting apoptosis signal regulating kinase 1/p38 signaling pathway via inactivating

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…[ 56 ] Studies have revealed a connection between inflammation and metabolic alterations in nucleus pulposus cells, which is in turn associated with LDH. [ 57 ] In the context of low back pain, there is a strong correlation between LDH and inflammation. [ 58 ] As mentioned earlier, there is a reduction in the survival of dorsal root ganglion neurons in cases of LDH, accompanied by an increase in both apoptosis and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 56 ] Studies have revealed a connection between inflammation and metabolic alterations in nucleus pulposus cells, which is in turn associated with LDH. [ 57 ] In the context of low back pain, there is a strong correlation between LDH and inflammation. [ 58 ] As mentioned earlier, there is a reduction in the survival of dorsal root ganglion neurons in cases of LDH, accompanied by an increase in both apoptosis and inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that p-p38 was highly expressed in ex vivo IVD, but collagen II was decreased. Additionally, several studies have suggested that targeting p38MAPK may be able to treat IDD [ 42 , 43 ]. The overall effect mechanism of TAK-715 in NPCs was described in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…LUM is an important ECM glycoprotein in human cartilage tissue and is highly expressed in nucleus pulposus specimens from patients with lumbar disc herniation. 63 Li et al 64 showed high expression of LUM in IDD, and LUM knockdown effectively attenuated tumour necrosis factor (TNF)-α-induced inflammatory response, cell cycle arrest, and cellular senescence. COL2A1 is a major component of type II collagen and plays an important role in maintaining the gel-like properties of nucleus pulposus tissues.…”
Section: Discussionmentioning
confidence: 99%